Experimental rice seed aging under elevated oxygen pressure: Methodology and mechanism - Prasad C. T., Manjunath; Kodde, Jan; Angenent, Gerco C.; de Vos, Ric C. H.; Diez-Simon, Carmen; Mumm, Roland; Hay, Fiona R.; Siricharoen, Sasiwimon; Yadava, Devendra K.; Groot, Steven P. C. (Frontiers in Plant Science, 2022)
Seed aging during storage results in loss of vigor and germination ability due to the accumulation of damage by oxidation reactions. Experimental aging tests, for instance to study genetic variation, aim to mimic natural aging in a shorter timeframe. As the oxidation rate is increased by elevating the temperature, moisture, and oxygen levels, this study aimed to (1) investigate the effect of experimental rice seed aging by an elevated partial pressure of oxygen (EPPO), (2) elucidate the mechanism of dry-EPPO aging and (3) compare aging under dry-EPPO conditions to aging under traditional moist-controlled deterioration (CD) conditions and to long-term ambient storage. Dry seeds from 20 diverse rice accessions were experimentally aged under EPPO (200 times higher oxygen levels), at 50% relative humidity (RH), along with storage under high-pressure nitrogen gas and ambient conditions as controls. While no decline in germination was observed with ambient storage, there was significant aging of the rice seeds under EPPO storage, with considerable variation in the aging rate among the accessions, with an average decline toward 50% survival obtained after around 21 days in EPPO storage and total loss of germination after 56 days. Storage under high-pressure nitrogen gas resulted in a small but significant decline, by an average of 5% germination after 56 days. In a second experiment, seven rice seed lots were stored under EPPO as compared to a moist-CD test and two different long-term ambient storage conditions, i.e., conditioned warehouse seed storage (CWSS) and traditional rice seed storage (TRSS). Untargeted metabolomics (with identification of lipid and volatile compounds profiles) showed a relatively high increase in levels of oxidized lipids and related volatiles under all four storage conditions. These compounds had a high negative correlation with seed viability, indicating oxidation as a main deteriorating process during seed aging. Correlation analysis indicated that EPPO storage at 50% RH is more related to aging under TRSS at 60% and CD-aging at 75% ERH rather than CWSS at 40% ERH. In conclusion, aging rice seeds under EPPO conditions is a suitable experimental aging method for analyzing variation among seed lots or genotypes for longevity under storage.